2020
DOI: 10.1002/jbmr.4124
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Bone Porosity in Rabbit Models of Osteoporosis

Abstract: Cortical bone porosity is intimately linked with remodeling, is of growing clinical interest, and is increasingly accessible by imaging. Thus, the potential of animal models of osteoporosis (OP) to provide a platform for studying how porosity develops and responds to interventions is tremendous. To date, rabbit models of OP have largely focused on trabecular microarchitecture or bone density; some such as ovariectomy (OVX) have uncertain efficacy and cortical porosity has not been extensively reported. Our pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 82 publications
(170 reference statements)
2
36
0
Order By: Relevance
“…Emerging collaborative SRμCT experiments performed at the CLS by Cooper's group and associated colleagues aim to address this limitation by combining rabbit animal models of bone remodeling with in vivo high‐resolution phase contrast imaging (Cooper, Harrison, Hiebert, & Andronowski, 2019; Hiebert et al, 2018). The authors have established that remodeling‐related resorption events can be visualized and subsequently tracked over imaging sessions (Cooper et al, 2019; Harrison et al, 2020). This advance has set the stage for the direct testing of hypotheses related to the steering of resorption events that initiate new osteon formation, and stimuli related to osteon morphology and dimensions.…”
Section: Technological Advancements In Bone Imagingmentioning
confidence: 99%
“…Emerging collaborative SRμCT experiments performed at the CLS by Cooper's group and associated colleagues aim to address this limitation by combining rabbit animal models of bone remodeling with in vivo high‐resolution phase contrast imaging (Cooper, Harrison, Hiebert, & Andronowski, 2019; Hiebert et al, 2018). The authors have established that remodeling‐related resorption events can be visualized and subsequently tracked over imaging sessions (Cooper et al, 2019; Harrison et al, 2020). This advance has set the stage for the direct testing of hypotheses related to the steering of resorption events that initiate new osteon formation, and stimuli related to osteon morphology and dimensions.…”
Section: Technological Advancements In Bone Imagingmentioning
confidence: 99%
“…In comparison to cancellous bone, cortical bone has two different bone remodelling patterns and more factors are likely to be involved in their regulation, so the importance of cortical bones is underestimated in most cases 31 . Some studies revealed that cortical bone undergoes a process of thinning cortical bone and increasing intracortical porosity 32 . In this study, the expanded pores were relatively common in the subendocortical region while cortical thickness remained stable.…”
Section: Discussionmentioning
confidence: 56%
“…Within the composite structure of bone, collagen acts as a framework, whereas bioapatite crystals serve as reinforcement between the collagen helices (Zhu et al, 2008;Reznikov et al, 2018;Binkley et al, 2020;Lee et al, 2020). Apart from its structural role, bioapatite plays a crucial role in calcium homeostasis serving as important reservoir of Ca and PO 4 ions (Heaney, 2006;Rigo et al, 2012 and references cited therein). In addition, bone is pervaded by a system of canals filled with nerves and blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…On a structural level, bone porosity constitutes one of the most important parameters that can provide information about the diagenetic history of a given bone, in particular because differences in porosity are closely related to changes of organic and/or inorganic components of bone. Bone porosity has thus been the subject of investigation for a long time, especially in osteoporosis research (e.g., Bjørnerem, 2016 and references cited therein;Harrison et al, 2020), but also in archaeology Nielsen-Marsh and Hedges, 2000a;Nielsen-Marsh and Hedges, 2000b;Turner-Walker et al, 2002). Commonly used destructive techniques for determining bone porosity on the nano-and micrometer scale are water sorption analyses and mercury intrusion porosimetry, with the latter technique also being used to determine pore size distribution Nielsen-Marsh and Hedges, 1999).…”
Section: Introductionmentioning
confidence: 99%